2012
DOI: 10.5402/2012/256261
|View full text |Cite
|
Sign up to set email alerts
|

The MainAeromonasPathogenic Factors

Abstract: The members of the Aeromonas genus are ubiquitous, water-borne bacteria. They have been isolated from marine waters, rivers, lakes, swamps, sediments, chlorine water, water distribution systems, drinking water and residual waters; different types of food, such as meat, fish, seafood, vegetables, and processed foods. Aeromonas strains are predominantly pathogenic to poikilothermic animals, and the mesophilic strains are emerging as important pathogens in humans, causing a variety of extraintestinal and systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
240
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(251 citation statements)
references
References 208 publications
2
240
0
9
Order By: Relevance
“…The results indicated that regardless of the ability to cause MC-LR degradation, the 40 bacterial isolates belonged to the Aeromonas genus (100% homology) (Figs 4 and 5B). This phenomenon could partly result from the activity of various pathogenic factors associated with Aeromonas, such as exotoxins, extracellular lytic enzymes, iron-binding and secretion systems, or an ability to survive low temperatures [40][41][42]. These factors might facilitate the total domination of Aeromonas in laboratory cultures.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that regardless of the ability to cause MC-LR degradation, the 40 bacterial isolates belonged to the Aeromonas genus (100% homology) (Figs 4 and 5B). This phenomenon could partly result from the activity of various pathogenic factors associated with Aeromonas, such as exotoxins, extracellular lytic enzymes, iron-binding and secretion systems, or an ability to survive low temperatures [40][41][42]. These factors might facilitate the total domination of Aeromonas in laboratory cultures.…”
Section: Resultsmentioning
confidence: 99%
“…When lacking shelter, snakes exhibit reduced energy intake (high regurgitation rate) and chronically elevated levels of corticosterone (CORT, a hormone secreted in response to stress via the hypothalamicepituitaryeadrenal, HPA, axis) Moore & Mason, 2001). However, some snakes do not experience an increase in baseline plasma CORT levels when occupying thermally suboptimal environments (Sykes & Klukowski, 2009; but see ; Dupoue, Brischoux, Lourdais, & Angelier, 2013). Furthermore, although little data on thermal performance exist for P. guttatus, the swimming and striking performances of other colubrid snakes are not highly sensitive to shifts in T b (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…LPS is separated into three domains: the extremely variable O-antigen polysaccharide which is linked to the core oligosaccharide that is in turn linked to the conserved and toxic lipid A component. Aeromonad lipid A and the core oligosaccharide have been recently described in an excellent review by Juan Tomás (Tomás, 2013). O-antigens are composed of oligosaccharide polymers of repeating units of 1-6 sugars, these variable units give rise to the wide variety of O-antigen groups (sergroups) that have been demonstrated in Gram negative bacteria.…”
Section: Lipopolysaccharidementioning
confidence: 99%